Perceptions of professional investors in Malaysia on the usefulness of quarterly financial reports - Ku Nor Izah Ku Ismail,; Roy Chandler, (Penerbit Universiti Kebangsaan Malaysia, 2005)
This study seeks to identify the perceptions of professional investors regarding the use and usefulness of corporate quarterly reports of companies in Malaysia. The findings show that quarterly reports are used and are useful, although the reports are not the most sought-after source of information. This paper provides evidence that the purpose of quarterly financial reports goes beyond forecasting the forthcoming annual results. The reports are also utilised, among other things, to predict results beyond the current period and to provide feedback information concerning financial performance for comparison with earlier expectations. This paper suggests that the relative usefulness of quarterly financial reporting would depend on the type of investors. Also, the findings may be useful to policy makers in preparing regulations on quarterly financial reporting as well as to provide opportunities for more research on the subject